Effects of a Mutation in the gyrA Gene on the Virulence of Uropathogenic Escherichia coli - Sánchez-Céspedes, Javier (Antimicrob Agents Chemother, 2015)
Fluoroquinolones are among the drugs most extensively used for the treatment of bacterial infections in human and veterinary medicine. Resistance to quinolones can be chromosome or plasmid mediated. The chromosomal mechanism of resistance is associated with mutations in the DNA gyrase- and topoisomerase IV-encoding genes and mutations in regulatory genes affecting different efflux systems, among others. We studied the role of the acquisition of a mutation in the gyrA gene in the virulence and protein expression of uropathogenic Escherichia coli (UPEC). The HC14366M strain carrying a mutation in the gyrA gene (S83L) was found to lose the capacity to cause cystitis and pyelonephritis mainly due to a decrease in the expression of the fimA, papA, papB, and ompA genes. The levels of expression of the fimA, papB, and ompA genes were recovered on complementing the strain with a plasmid containing the gyrA wild-type gene. However, only a slight recovery was observed in the colonization of the bladder in the GyrA complement strain compared to the mutant strain in a murine model of ascending urinary tract infection. In conclusion, a mutation in the gyrA gene of uropathogenic E. coli reduced the virulence of the bacteria, likely in association with the effect of DNA supercoiling on the expression of several virulence factors and proteins, thereby decreasing their capacity to cause cystitis and pyelonephritis.